Empowerment – a Double Edged Sword? - Beinaroviča, Ieva Daniela; Kleins, Druvis (Socialiniai tyrimai, 2015)
The concept of empowerment is a democratic tool and a logical next step in the evolution of public administration. In this article we explore the possibility of this concept to be used as a tool of unconventional warfare under a certain set of conditions. The carried out case study of the recent events in Ukraine, Crimea allows to conclude that empowerment can indeed be used to compromise the territorial integrity of a sovereign country.
Keywords: empowerment; unconventional warfare; Ukraine; Crimea